2017
DOI: 10.6007/ijarbss/v7-i8/3230
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Parental Education on Academic Performance of Secondary School Students in Kuala Terengganu

Abstract: This study aims to examine how parental education influence students' academic performance. The main objective of the study is to analyse how parental education and parental educational qualification significantly affect secondary school students' academic performance in Kuala Terengganu, Malaysia. Descriptive Survey Research design was used in which data from 200 respondents was collected using self-administered questionnaire from 4 selected secondary schools within Kuala Terengganu. A stratified random sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 0 publications
4
17
0
Order By: Relevance
“…Parents of the high socioeconomic class are participating in the academic activity of their children, and they support their children to successful learning, they pay more attention to the academic progress of children, they regularly interact with their teacher, manage the children's school absence and other difficulties. Bakar et al (2017) also support the argument that children of educated parents get these advantages than the children of uneducated parents. Sewell and Hauser (1993) further added the performance of junior students has significantly affected by parent's education.…”
Section: Parental Education and Academic Performance Of Childrensupporting
confidence: 73%
“…Parents of the high socioeconomic class are participating in the academic activity of their children, and they support their children to successful learning, they pay more attention to the academic progress of children, they regularly interact with their teacher, manage the children's school absence and other difficulties. Bakar et al (2017) also support the argument that children of educated parents get these advantages than the children of uneducated parents. Sewell and Hauser (1993) further added the performance of junior students has significantly affected by parent's education.…”
Section: Parental Education and Academic Performance Of Childrensupporting
confidence: 73%
“…This study is in line with Rothestein (2004), Hill et al (2004), who argue that children from parents with higher education level are more curious about learning compared to those from parents with low levels of education. Other studies supporting this result are studies by Abubakar et al (2017) and Khan et al (2015) who found that students from parents with a higher level of education achieve better in learning than those from parents with low levels of education.…”
Section: Discussionmentioning
confidence: 72%
“…The illiterate parents faced many difficulties in being involved in their children's education (Menheere and Hooge, 2010). Students from highly educated parents achieved higher academic grades than students of low educated parents (Bakar et al, 2017). The findings of Bierman et al (2015) supported these results that the level of parental education is the major determinant in children's educational outcomes, frequency and quality of how parents use home learning materials to shape the academic performance of their children.…”
Section: Discussionmentioning
confidence: 92%